Mechanism And Rate Limiting Step For The Catalytic Decomposition Of Methane To Hydrogen And Carbon Nanotube. - Sharif Zein, Sharif Hussein; Mohamed, Abdul Rahman; Talpa Sail, P. Sesha; Mohd Zabidi, Noor Asmawati

(untitled)
The main focus of this paper is to report a mechanism, a rate-limiting step, and a rate law consistent with experimental observation for the decomposition of methane to hydrogen and carbon nanotube over Ni/Mn based catalyst.